Single underwater image enhancement based on adaptive correction of channel differential and fusion - Zhao, Zefeng; Zhou, Zhuang; Lai, Yunting; Wang, Tenghui; Zou, Shujie; Cai, Haohao; Xie, Haijun (Frontiers in Marine Science, 2023)
Clear underwater images are necessary in many underwater applications, while absorption, scattering, and different water conditions will lead to blurring and different color deviations. In order to overcome the limitations of the available color correction and deblurring algorithms, this paper proposed a fusion-based image enhancement method for various water areas. We proposed two novel image processing methods, namely, an adaptive channel deblurring method and a color correction method, by limiting the histogram mapping interval. Subsequently, using these two methods, we took two images from a single underwater image as inputs of the fusion framework. Finally, we obtained a satisfactory underwater image. To validate the effectiveness of the experiment, we tested our method using public datasets. The results showed that the proposed method can adaptively correct color casts and significantly enhance the details and quality of attenuated underwater images.